POLA ASUH ORANG TUA DALAM PEMBENTUKAN KARAKTER ANAK DI DESA DUREN DAN SRUWEN - Solihin Solihin; Khoiruddin Nasution; Ma'mun Efendi Nur (Jurnal Progress: Wahana Kreativitas dan Intelektualitas, 2022)
The aims of this study are: 1) To analyze parenting patterns in the formation of children's character in Duren Village and Sruwen Village; 2) To analyze the influence of parenting style on the character formation of children in Duren Village and Sruwen Village; 3) To analyze the similarities and differences in parenting styles in shaping the character of children in Duren Village and Sruwen Village; 4) To analyze the construction of parenting patterns in shaping the character of today's millennial children. The type of research carried out by the author is field research. The researcher uses a mixed/combined research methodology. The results of the research are: 1) Parenting patterns in Duren Village are authoritative parenting patterns, namely parents who apply democratic parenting patterns have clear rules and expectations and parenting patterns in Sruwen Village are authoritarian parenting patterns where parents are central, namely central. all words/words as well as the will of parents are used as standards that must be obeyed by children; 2) The parenting pattern of Duren Village's parents has a positive and significant effect on the character building of Duren Village children, because Duren Village's parenting style prioritizes an important role in determining the character formation of Duren Village children. The parenting pattern of Sruwen Village parents has a positive and significant effect on the character formation of Sruwen Village children, this is due to parents who do not apply the rules/norms in the family/household and also there is a good relationship atmosphere between children and their parents so that children become disaffected. comfortable in interacting with family and parents who tend to educate their children in an authoritarian way.; 3) Parents in Duren Village in shaping children's character through behaviors that are very effective in directing children. While the parenting pattern in Sruwen Village in raising their children is more concerned with the wishes of the parents, the children are monitored quite closely, the attitude of parents always keeps their distance from their children rather than considering the wishes of their children; 4) The construction of parenting patterns in shaping the character of children in Duren Village and Sruwen Village and its relevance in dealing with today's millennials are as follows: exemplary parenting, advice parenting, parenting with attention or supervision through communication as a transaction that consists of: knowing the purpose, knowing the opponent / partner talking, respect and empathy.